CHARACTERISATION OF TOBELITE RIETVELD REFINEMENT OF XRD SPECTRA - Harlov D.E.; Andrut M.; Pöter B. (My University, 2001)
Tobelite (NH4) Al2 [AlSi3O10] (OH)2, the ammonium analogue of muscovite, and its deuterated form ND4-tobelite (ND4) Al2 [AlSi3O10] (OD)2 have been synthesised at 600 °C and 200 and 500 Mpa using a well homogenised, stoichiometric SiO2-Al2O3 oxide mix with Al2O3 in excess of 5 mol% and a 25% NH3 solution whose relative abundance was such that the amount of NH4+ stoichiometrically available was in excess of 50%. Characterisation of both tobelite and ND4-tobelite using IR-spectroscopy, Rietveld refinement of X-ray powder diffraction data, and electron microprobe analysis indicate that, similar to K+ in muscovite, the NH4+ or ND4+ molecule occupies the interlayer site. IR absorption bands caused by NH4+ and ND4+ can be explained, to a very good approximation, on the basis of Td symmetry. Nevertheless, substantial line broadening and the occurrence of shoulders indicate a deviation from ideal Td symmetry. However, even at 77 K, no discrete splitting of the degenerate states could be confirmed. The OH stretching frequencies observed for synthetic tobelite are quite similar to those for muscovite, indicating that the replacement of K+ by NH4+ has no effect. The low FWHH of the OH bands indicate that the hydroxyl groups are well ordered within the structure. Rietveld refinement of tobelite and ND4-tobelite indicates that all samples synthesised consist of the 3 different mica polytypes which are typical of muscovite – namely 1M (C2/m), 2M 1 (C2/c) and 2M 2 (C2/c). Tobelite and ND4-tobelite synthesised at 500 Mpa principally contain the 1M polytype, whereas the principle polytype for ND4-tobelite synthesised at 200 Mpa, is 2M 2. Rietveld refinement of X-ray diffraction spectra for tobelite synthesised at 200 Mpa was problematic due to the very broad FWHH of the X-ray peaks indicating poor crystallinity. In comparision to synthetic muscovite, the cell dimensions observed for tobelite and its deuterated analogue are quite similar except for the lattice constant c. Due to the larger radius of NH4+ or ND4+ compared to K+ cation, the c-direction is expanded form 10.275 Å in muscovite to approximately 10.540 Å in tobelite and ND4-tobelite.